Detection of exogenous Jaagsiekte sheep retrovirus in Turkey - Can-Sahna, Kezban; Eroksuz, Yesari; Berber, Engin; Sozdutmaz, Ibrahim (Agricultural Research Communication Centre, 2015)
The aim of this study is to detect the exogenous Jaagsiekte sheep retrovirus (exJSRV) in suspected cases of ovine pulmonary adenocarcinoma (OPA) from the Eastern Anatolian region of Turkey. Pathological examination and PCR were carried out with the lung, lymph nodule, brain, heart and liver tissues of four sheep with suspected OPA. Histology of the lung sections indicated the well-circumscribed, multifocal and unencapsulated gray to white masses (arrows) on the parietal surface of medial and caudal lobes. exJSRV was detected in all tissue samples except for brain by nested polymerase chain reaction (nPCR). In addition to the nested-PCR results, the presence of exJSRV into the clinical samples was confirmed with sequencing of two PCR-positive products for OPAV. This report highlights the first presence of exJSRV in the sheep suspected with OPA in Turkey. Furthermore, the results provide supporting evidence for the metastasis of exJSRV in extra-thoracic tissues.
Keywords: exJSRV; OPA; PCR; Sheep